PENETUAN RADIUS BULIR DARI FOTOMETRI ASTRONOMI: PERBANDINGAN TIGA METODE BERBASIS MODEL MIE - Nuning Nuraini; Hakim L. Malasan; Tri W. Hadi (Lembaga Penerbangan dan Antariksa Nasional, 2004)
This paper discusses modeling steps of the total extinction coefficients,deduced from the astronomical photometric observations, to estimate aerosol perticulate size in the atmospheric layer. One important step in modeling is the application of Mie theory through Wempe's extinction law for aerosol and introduced by Angstrom (1929), i.e. The factor Qext is derived by elaborating Mie theory, through extinction efficiency factor which has been normalized, and an assumption that particle size is represented by a log-normal distribution. Final result of aerosol radius is deduced by fitting a decomposed observed extinction coefficient with that computed using the three Mie theory developed to estimate the best aerosol particulate's size.